THE ROLE OF INFAQ IN BASIC EDUCATION DEVELOPMENT IN THE ACEH COMMUNITY - Maemonah, Maemonah; Yuliawati, Fitri; Hasanah, Azizah Uswatun (UIN Sunan Kalijaga Yogyakarta, 2021)
After the tsunami disaster and Aceh political reconciliation, awareness of education’s importance began spreading to the villages. The awareness creation process is preferable because the prominent supporters of this effort are the people only. At the same time, the Indonesian government’s role is also active in gaining a positive image in the province. Therefore, this paper investigated the level of community awareness in setting aside a portion of the members’ income to build elementary schools, pay teacher salaries, and meet other educational needs. The result showed that the community movements were not positively correlated with management and awareness-raising and the general donation movement in Aceh. Besides, community education empowerment has been fast considering various possible future challenges to be encountered. Nevertheless, the targeted awareness has not been accompanied by public attention towards building higher-quality educational facilities and infrastructure.